Adherence to a moderate sodium restriction diet in outpatients with cirrhosis and ascites: a real‐life cross‐sectional study. (21st May 2014) - Morando, Filippo; Rosi, Silvia; Gola, Elisabetta; Nardi, Mariateresa; Piano, Salvatore; Fasolato, Silvano; Stanco, Marialuisa; Cavallin, Marta; Romano, Antonietta; Sticca, Antonietta; Caregaro, Lorenza; Gatta, Angelo; et al.
Summary Background & Aims A moderate sodium restriction diet should be indicated in patients with cirrhosis and ascites. Nevertheless, there is a lack of specific investigation on its correct application. To evaluate the adherence of patients with cirrhosis and ascites to a moderately low‐salt diet and the impact on intake of total calories and serum sodium concentration. Methods A total of 120 outpatients with cirrhosis and ascites were interviewed with a pre‐established questionnaire. A quantitative assessment of nutrient and salt intake was performed. Result A moderately low‐salt diet was followed by 37 patients (Group A). Of the 83 patients who did not follow the diet (Group B), 54 thought that they were following it. The mean daily sodium intake was 79.5 ± 5.5 mmol/day (Group A) and 205.9 ± 14.1 mmol/day (Group B), P < 0.0001. The adherence to diet was related to the severity of cirrhosis, and was higher among candidates for liver transplantation and in patients followed through the Care Management Program. Patients of Group A had reduced the mean daily calorie intake by 20% compared with Group B patients (P < 0.0005), while there was no difference on the occurrence of hyponatraemia. Conclusions This study shows a poor adherence of patients with cirrhosis and ascites to a moderate dietary sodium restriction. Adherence to a diet seems to increase with the worsening of liver disease, probably because of the reduction of alternative therapeutic options. In addition, a deficiency in the educational process can lead the patient to follow a sodium‐reduced diet by means of dangerous tools, such as reducing the overall daily food intake.